The Speaking Skill by Using Slang Words in a Movie through Mind-Mapping Strategy - Baiatun Nisa; Sulhizah Wulan Sari; Rr Nabila Wahyu Apriyanti; Paramita Kusumawardhani (LPPM Universitas Bina Sarana Informatika, 2023)
The main objective of this study is to apply the teaching of speaking English through mind mapping strategy for the students at the English Department of Bina Sarana Informatika University. The participants included 20 students in the third semester. Speaking is an important skill in English language learning which is used by the students to communicate in their class and daily activities as a way of learning practice. By this mind mapping strategy, this paper aims at showing that this strategy can be implemented to get active speaking skills. This research uses a qualitative method to describe the practice application of classroom observations and the emerging themes of the original slang words gained through watching a movie. The data were carried out by observing, documenting, and interviewing students about the speaking teaching-learning process in the classroom using the English slang words in a movie with a mind-mapping strategy. The data was analyzed and focused on classroom practice directly related to the use of slang words in a movie and the mind-mapping strategy. The results showed that implementing a mind-mapping strategy through slang words in a movie can be conducted by knowing the meaning of the slang word in the movie, mapping the slang word into the sentence, and practicing the slang word in the student’s conversation. This mind-mapping strategy is effective in helping the EFL students to enrich their vocabularies, enhance their memory in making conversation, and remember the material easier and more creatively.